2015
DOI: 10.1038/mp.2015.162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxytocin nasal spray on social interaction deficits observed in young children with autism: a randomized clinical crossover trial

Abstract: Interventions for autism are limited. The synthetic hormone oxytocin may provide a potential treatment to improve core social and behavioral difficulties in autism, but its efficacy has yet to be evaluated in young children who potentially may benefit to a greater extent. We investigated the efficacy, tolerability and safety of oxytocin treatment in young children with autism using a double-blind, randomized, placebo-controlled, crossover, clinical trial. Thirty-one children with autism received 12 Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
272
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(296 citation statements)
references
References 37 publications
14
272
1
7
Order By: Relevance
“…Human studies have focused on pharmacological administration and the measurement of plasma neuropeptides, mainly of OXT. It has been suggested that intranasal OXT is beneficial for the remission of autistic symptoms by improving cooperation and sense of trust [15] as well as by enhancing social responsiveness [16] and social reciprocity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have focused on pharmacological administration and the measurement of plasma neuropeptides, mainly of OXT. It has been suggested that intranasal OXT is beneficial for the remission of autistic symptoms by improving cooperation and sense of trust [15] as well as by enhancing social responsiveness [16] and social reciprocity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials of OT in autistic patients are ongoing, yet several studies have produced inconclusive results (4)(5)(6)(7)(8), demanding improvements to the efficacy and reliability of OT-based therapeutics. One strategy is to take advantage of existing physiological pathways in the brain that regulate OT activity to combinatorially enhance the oxytocinergic effects on social functions.…”
mentioning
confidence: 99%
“…Although seeing improvement in specific social behaviors inside a laboratory is an important first step, research also needs to demonstrate that oxytocin nasal spray can improve day-to-day social functioning in the real world, with long-term daily use. Early research has shown that taking oxytocin nasal spray over 5 weeks led to small improvements in social behavior in young children with ASC [5]. However, other research in older children and adults with ASC has not shown any improvements after similar periods of taking oxytocin.…”
Section: Oxytocin As a Treatment?mentioning
confidence: 99%